EFFECT OF REDUCING SUNFLOWER CAKE AND SEEDS DEGRADABILITY ON PUBERTY AND TESTICULAR MEASUREMENTS Of AWASSI LAMBS - S, Safwan. L.; Almallah, O. D. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted to elucidate the effect of lowering sunflower cake degradability or seeds on puberty, testicular and blood measurements of Awassi lambs. Thirty Awassi lambs with an average body weight of 25.93 ± 0.42 kg and 3- 4 months old. Lambs were divided into three groups (10 lambs in each group) the first group was fed a diet contained 11% of sunflower cake (T1), the second group was fed a diet contained 11% of low degradable sunflower cake (T2), while the third group fed a diet that contained 11% of low degradable sunflower seeds (T3). The results indicated that reduce sunflower seeds degradability in (T3) led to a significant increase (p≤ 0.05) in the length of right and left testes (8.35 and 8.30 cm) respectively as compared to the T1 (7.84 and 7.77 cm) respectively and T2 (7.88 and 7.63 cm) respectively, scrotum volume increased significantly (p≤ 0.05) in the T3 165.72 cm3 as compared to the T2 151.86 cm3, Testosterone hormone concentration increased significantly (p≤ 0.01) in T3 2.81 ng/ml as compared to the T1 and T2 ( 1.455 and 1.75 ng/ml) respectively . Also, feeding lambs with low degradable sunflower cake (T2) and seeds (T3) enhance significantly (p≤ 0.05) seminiferous tubule diameter, germinal epithelium height, and Sertoli cells count as compared to lambs that fed sunflower cake (T1). The results indicate that reducing degradability of protein and fat sources rich in unsaturated fatty acids in the diets of lambs before puberty had a positive role in testicular development and testosterone hormone secretion at puberty.